Excedente emocional y ampliación de lo político en Chile. Análisis visual del movimiento estudiantil 2011-2014 (Altre Modernità, 2016)
The question of emotions and politicization processes are at the heart of concern and discussion in this article. In turn, and in the specific, emotions - protest - policy are also an unavoidable methodological shift: from the verbal language to the visual language. We propose to enter this communication from the visual images produced and deployed by social actors in the mobilization chilean context that stage of circumstantial way possible expansion and redefinition of politics regarding the territories, actors and procedures involved.